Dampak Kebijakan Pemerintah terhadap Pemerataan dan Kualitas Tenaga Pendidik Pendidikan Anak Usia Dini (PAUD) - Ananda, Salwaa Annaafi; Ismaniar, Ismaniar; Putri, Lili Dasa (Jurnal Pendidikan Dirgantara, 2025)
This study examines the impact of government policies on the distribution and quality of Early Childhood Education (ECE) teachers in Indonesia, as a crucial component in efforts to improve the quality of education services during the golden age. Governmment policies such as the Minister of Education and Culture Regulation No. 137 of 2014 concerning National PAUD Standards, tiered training, teacher certification, Teacher Professional Education (PPG), and the Teacher Mover program have significantly contributed to improving educator competency. However, the implementation of these policies still faces various obstacles, particularly related to the unequal distribution of educators between urban and 3T areas, limited access to education, and the low welfare of non-civil servant teachers. The study results indicate that government policies have increased teacher awareness of the importance of academic qualifications and professional competencies, but the impact on equity has not been optimal due to geographical factors and unequal regional support. This analysis emphasizes the need to strengthen the data-based teacher needs mapping system, improve ongoing training programs, and provide more appropriate welfare support for PAUD teachers. Therefore, collaboration between the central government, regional governments, professional organizations, and the community is key to ensuring the distribution of educators and improving the quality of PAUD services nationally. This study is expected to serve as a reference in developing more effective and equitable policies for PAUD educators in Indonesia.